Study of patterns of maxillofacial injuries: An institution-based observational study - Leslie Sara Mathew Kalathil; Ummar Mangalath; A Roshni; Sachin Aslam; Tom Thomas; Rakesh B Nair (Wolters Kluwer Medknow Publications, 2021)
Maxillofacial fractures are one of the common presentations in an emergency department. They are considered to be one of the significant and dominant conditions that requires treatment as the fractures can result in morbidity, mortality, psychological, functional disability, and facial mutilation. The incidence, patterns, and etiology of maxillofacial fractures vary from one country to another due to the geographical, cultural, social, and economic differences. The present study included 176 patients from January 2019 to September 2020 that aimed to evaluate the pattern of maxillofacial fractures and to learn the etiology for the same.